Holocene sedimentary evolution of the Mekong River floodplain, Cambodia. (1st February 2021) - Ishii, Yuji; Tamura, Toru; Ben, Bunnarin
Abstract: The Mekong River, which has high economic and ecological importance, has an extensive floodplain and delta plain that extends from Cambodia to Vietnam. Understanding the Holocene evolution of the fluvial system is needed in order to predict the future development of the system and develop a strategy to guide the sustainable management. This paper reconstructs the Holocene sedimentary evolution of the Mekong River floodplain, Cambodia, from 12 auger cores and 69 optically stimulated luminescence ages, and compares the reconstructed floodplain history with that of other large river systems. Rapid deposition of thick crevasse splays implies floodplain aggradation in response to sea-level rise before 6.5 ka. After 6.5 ka, when the sea-level reached a stillstand, the rapid aggradation ceased and levee and crevasse-splay deposition were localized near the anastomosing river channels. The rate of levee accretion was very low in the anastomosing river system (<1 m/kyr), which implies that the riverbed aggradation caused by sea-level rise before 6.5 ka outpaced levee accretion and led to avulsion by diversion into the floodbasin. Some distributary channels were abandoned around 4 ka, corresponding to a shift from an anastomosing to a single-channel river system. This shift might be attributed to an abrupt decrease in precipitation caused by weakening of the East Asian and Indian summer monsoons. Downstream of Phnom Penh, rapid levee deposition started on the uppermost delta plain after 1 ka while rapid lateral migration of the river channel occurred upstream. These increased fluvial activities correspond to accelerated mud accretion of the Mekong delta coast and potentially reflect an increase in sediment supply caused by human activities. The evolution of the Mekong River floodplain might be comparable with other large river systems in the EASM, ISM, and African monsoon regions, where a substantial weakening of the summer monsoon and hence a decrease in precipitation occurred in response to declining summer insolation in the middle to late Holocene. Highlights: OSL dating provides chronology for the evolution of the lower Mekong River floodplain. Pre-6.9-ka sea-level rise led to rapid fluvial aggradation by crevassing and avulsion. Monsoon change at ∼4 ka altered the system from anastomosing to single-channel river. Human-induced increase in sediment discharge increased fluvial activities after 1 ka.